Meta-Analysis of the Relationship Between Learning Media in Hybrid Learning and Critical Thinking and Creativity in Science - Ayu, Hena Dian; Saputro, Sulistyo; Sarwanto, Sarwanto; Mulyani, Sri (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
The 21st-century learning paradigm is characterized by integrating technology into learning facilitating flexible and accessible learning experiences. One such model is hybrid learning, enabling education to transcend time and place with technological aid. Amidst this backdrop, it is crucial that hybrid learning provides education and fosters essential skills of the 21st century, including critical thinking and creativity. This research endeavors to establish a connection between the learning media employed in hybrid learning and the enhancement of critical thinking and creativity skills within the Science and STEM education context. The study also investigates the utilization of laboratory-based applications in chemistry instruction. Employing a meta-analysis approach with descriptive analysis methods, the researchers scrutinized 50 articles cataloged in Scopus, focusing on publications from the past decade. The meta-analysis findings unveil a significant effect size of 0.87, indicating a substantial correlation between the use of learning media and the cultivation of critical thinking skills. Moreover, the association between hybrid learning's learning media and creativity skills is evidenced by an effect size of 0.94. Consequently, it can be inferred that a substantial correlation exists between learning media in hybrid learning and the development of creativity and critical thinking abilities. The impact of laboratory-based applications and software in science education, particularly chemistry, is greatly influenced by pedagogical aspects and instructional strategies.